Polygamous Marriage Law Reform in Indonesia: A Socio-Legal Analysis of Substantive Justice in Islamic and National Law - Adde Ramadhani; Abdul Halim; Risnita Risnita (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
One of the most contentious topics in modern Islamic family law is polygamous marriage, especially in plural legal systems like Indonesia where national laws and human rights concepts collide with religious standards. With an emphasis on the pursuit of substantive justice within both Islamic and national legal paradigms, this study uses a socio-legal framework to analyze Indonesia's reform of polygamous marriage law. In order to evaluate the efficacy of current legal regulations, such as Law No. 1 of 1974 as amended by Law No. 16 of 2019 and the Compilation of Islamic Law, this study combines the principles of maqāṣid al-sharīʿah with socio-legal theory, drawing on normative-theological analysis and qualitative doctrinal research. The results show that normative legal ideals and actual socio-legal reality continue to diverge. The ability of statutory rules to provide women and children with meaningful protection is limited because, although they set stringent procedural requirements to prevent polygamy, their execution frequently remains formalistic and institutionally constricted. Furthermore, the achievement of justice as envisioned in Islamic ethical principles is undermined by the persistence of dominant patriarchal legal cultures in influencing judicial procedures and public attitudes. In order to reframe polygamy as a conditional socio-ethical institution rather than an inalienable legal privilege, this paper suggests a reform-oriented legal framework. The study promotes a contextualized view of Islamic law that is consistent with both international human rights norms and constitutional ideals by placing a strong emphasis on substantive justice, gender fairness, and public benefit. The results provide policy-relevant insights for creating a more just and socially responsive family law system in Indonesia and add to the ongoing discussions on Islamic legal reform.